Fabrication and characterization of polycaprolactone/chitosan nanofibers containing antibacterial agents of curcumin and ZnO nanoparticles for use as wound dressing - Mosallanezhad, Pezhman; Nazockdast, Hossein; Ahmadi, Zahed; Rostami, Amir (Frontiers in Bioengineering and Biotechnology, 2022)
The potential of the nanoscale structure is utilized by electrospun nanofibers, which are promising materials for wound dressings. Here, we prepared wound dressings constituting polycaprolactone (PCL) and chitosan (CS). Curcumin (Cur) and zinc oxide nanoparticles (ZnO) as antibacterial agents were embedded in PCL/CS electrospun nanofibers and different properties including morphology, physicomechanical, interaction with water, antibacterial efficiency, and in vitro studies were investigated. SEM images confirmed the nanofibrous structure of samples with 100 ± 5 to 212 ± 25 nm in average diameter. Elemental analysis of nanofibers showed a good distribution of ZnO along nanofibers which not only caused decreasing in nanofiber diameter but also increased tensile strength of nanofibers up to 2.9 ± 0.5 MPa and with good elongation at break of 39 ± 2.9. ZnO nanoparticles also facilitated the interaction of nanofibers with water, and this led to the highest water vapor transition rate, which was equal to 0.28 ± 0.02 g cm−2 day−1. The sample containing 3 wt% Cur had the highest water uptake value (367 ± 15%) and the lowest water contact angle (78 ± 3.7°), although Cur has a hydrophobic nature. The release profile of Cur showed a two-stage release and the Peppas model predicted a non-fickian diffusion. Simultaneous incorporation of CS, ZnO, and Cur effectively inhibited bacterial growth. In addition, in vitro studies represented that high content of Cur decreases cell viability and cell attachment. The outcomes from the fabricated nanofibrous scaffolds demonstrated appropriate properties for application as a wound dressing.